JAEPL, Vol. 13, Winter 2007-2008 - Kristie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
Essays Bell Hooks. Writing for Reconciliation: A Musing Devan Cook. The Value of Mutual Respect: What We Learn from Student Complaints . This essay discusses the emotional labor of teaching and the ways writing programs can support that work. Elizabeth Gardner, Patricia Calderwood, and Roben Toroysan. Dangerous Pedagogy Using data primarily drawn from undergraduate psychology classes, we reflect upon what humane but "dangerous" pedagogy illustrates about our teaching and our students' learning. Karen Surman Paley. Applying "Men and Women for Others" to Writing about Archeology. This essay explores one archeology professor's pedagogy of caring during a summer field study of a former state school and orphanage. Elizabeth Oakes and others. Reading Othello in Kentucky. Members of a graduate Shakespeare class at Western Kentucky University discuss Otherness in the context of Othello and national perceptions of Kentucky. Rachel Forrester. The "Not Trying" of Writing. A very spiritual "not trying," or non-work, is at the heart of composition. Eudora Watson, Jennifer Mitchell, and Victoria Levitt. The Other End of the Kaleidoscope: Configuring Circles of Teaching and Learning. To reflect on and participate in reconsideration of convention in academic discourse, this essay presents three voices in three genres. Helen Walker. Connecting. Steven DeGeorge —The Things They Bring to School . Johanna Rodgers —Translating Authority Jeremiah Conway —Emily's Cave Reviews Kabi Hartman. Writing With, Through and Beyond the Text: An Ecology of Language. (Rebecca Luce-Kapler, 2004) Caleb Corkery. African American Literacies Unleashed: Vernacular English and the Composition Classroom. (Arnetha F. Ball and Ted Lardner, 2005) Joel Kline . Race, Rhetoric, and Technology: Searching for Higher Ground. (Adam J. Banks, 2006) Terri Pullen Guezzar. Why Is Corporate America Bashing Our Public Schools? (Kathy Emery and Susan Ohanian, 2004)